(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Not much attention has been paid to the identification of morphological changes in the face-jaw area in children with chronic diseases of the respiratory system. Orthodontic dentist, ENT, pediatric specialists did not work together. In order to eliminate anomalies and deformations of the tooth-jaw system, orthodontic dentists carried out treatment measures without paying attention to their etiology. Today, attention has been paid to the treatment of changes in the face-jaw area in children with chronic diseases of the respiratory system, anomalies and deformations of the tooth-jaw system. Analysis of morphological changes in the upper jaw in mouth-breathing children, clinical examinations, anthropometric analysis of control diagnostic models separately for each patient, as well as analysis of X-ray data (orthopantomography and teleroentgenography). Evaluating the economic and medical effectiveness of our research.